2021
DOI: 10.1371/journal.pone.0247563
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Diaporthe eres, the causal agent of hazelnut defects

Abstract: Diaporthe eres has been recently reported as the causal agent of hazelnut defects, with characteristic brown spots on the kernels surface and internal fruit discoloration. Knowledge regarding the ecology of this fungus is poor but, is critical to support a rationale and effective hazelnut crop protection strategy. Therefore, a study was performed to describe and model the effect of different abiotic factors such as temperature (T, 5–35°C, step 5°C) and water activity (aw 0.83–0.99, step 0.03) regimes on D. ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Our results showed that all species identified in this study reached maximum colony diameter at 25–30 °C and preferred to grow under low acidic to alkaline rather than acidic medium. The observations in the present study are consistent with the results of Arciuolo et al [ 51 ] and Hilário et al [ 12 ]. In the future, these abiotic factors could be used as the basis for developing a predictive model for the infection of Diaporthe taxa of tea plants in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results showed that all species identified in this study reached maximum colony diameter at 25–30 °C and preferred to grow under low acidic to alkaline rather than acidic medium. The observations in the present study are consistent with the results of Arciuolo et al [ 51 ] and Hilário et al [ 12 ]. In the future, these abiotic factors could be used as the basis for developing a predictive model for the infection of Diaporthe taxa of tea plants in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
“…Only a few studies have shown the effect of environmental factors on the growth of Diaporthe species. The most recent study was carried out by Arciuolo et al [ 51 ], who tested the optimal temperature and water activity required for mycelial growth, pycnidial conidiomata development, and asexual spore production of D. eres , the causal agent of hazelnut defects. Arciuolo et al [ 51 ] concluded that the optimum temperature for mycelial growth of D. eres was observed at 20–25 °C and at 30 °C for pycnidia and cirrhi development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Anisogramma , Anthostoma , Diaporthe , Diaporthella , Diplodia , Dothiorella , and Gnomoniopsis are common fungi that inhabit branches in hazel trees in America, Chile, Italy, and Turkey ( Gottwald and Cameron, 1980 ; Guerrero and Pérez, 2013a ; Linaldeddu et al., 2016 ). Alternaria , Aspergillus , Botryosphaeria , Colletotrichum , Diaporthe , Fusarium , Pestalotiopsis , and Phoma are often isolated from fruits, especially in Turkey and the Caucasus region ( Sezer and Dolar, 2016 ; Battilani et al., 2018 ; Arciuolo et al., 2020 ; Arciuolo et al., 2021 ). Although little information is available, Cytospora corylicola generally occurs in hazelnut growing areas in Europe ( Salerno, 1961 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on D. eres in Greece showed that this pathogen has an optimal growth at 25 °C, however, considerable mycelial growth was assessed within the range 20-30 °C (Thomidis and Michailides 2009). Other analyses on water availability and relative humidity confirmed the influence of these abiotic factors on D. eres mycelial growth and conidia germination (Arciuolo et al 2021). Wet and humid conditions have been reported as favourable also for Paraconiothyrium fuckelii development (Martin et al 2017).…”
Section: Discussionmentioning
confidence: 93%